A New Method Based on One Dimensional Diffusion Using Small Glass Tubes for the Measurement of Fibrinolytic Activity - Yasukouchi, Taro, M. D.; Watanabe, Takeo, M. D. (Thrombosis and Haemostasis, 1972)
A new method of estimating fibrinolytic activity is introduced. This method based on one dimensional diffusion (simple diffusion) is characterized by adopting small glass tubes, internal diameter about 3.5 mm calibrated from the bottom by 50 mm, as containers of substratecl fibrin.The results and advantages over previous methods are as follows :1. Clear line of demarcation between lyzed zone and remaining fibrin makes it easier to measure the extract of lysis than in the fibrin plate method.2. The enzyme activity of materials tested is kept stable for many hours.3. The quantity of test material in the fibrin tube is optional.4. Only 1/10 fibrinogen required for fibrin plate method is sufficient.5. Adopting a standard euglobulin unit gives a free choice of experimental conditions. The pooled euglobulin prepared from 48 healthy persons represented 1 standard euglobulin unit.Standard deviations of “Euglobulin + Streptokinase” level in plasmas from 24 healthy men (aged 18-54 yrs) and women (aged 17-50 yrs) were ±0.27 and ±0.20 standard euglobulin units, respectively.